CHEMICAL STABILITY AND SORPTION PROPERTIES OF ANIONITE BASED ON LOCAL RAW MATERIALS AND WASTE (Scientific journal of the Fergana State University, 2023)
This paper presents the results of the chemical modification of polyvinyl chloride (PVC) with monoethanolamine-containing waste[1,1231-1236b], the optimal conditions for obtaining a new type of anion exchanger, the chemical stability of the obtained anion exchanger, and the sorption of KMnO4 ions at various temperatures. Isothermal models were used to represent the adsorption mechanism of equilibrium processes. According to the Langmuir isotherm model calculated on the basis of the obtained results, qemax = 125 (293K) mg/g, which indicates a high sorption of Mn  ions by the new ion exchanger.